2018
DOI: 10.1177/1526602818783989
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Intravascular Lithotripsy for Treatment of Below-the-Knee Arterial Stenoses

Abstract: Purpose: To evaluate the safety and feasibility of treating calcified infrapopliteal stenoses using an intravascular lithotripsy (IVL) system. Methods: The Disrupt BTK study was a prospective, nonrandomized, multicenter, feasibility, and safety trial that enrolled 20 patients (mean age 79.0±9.6 years; 14 men) at 3 participating sites (ClinicalTrials.gov identifier NCT02911623). Fifteen patients had Rutherford category 5 ischemia, and all patients had moderate to severe below-the-knee arterial calcification. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 10 publications
2
88
0
2
Order By: Relevance
“…The Lithoplasty system received FDA approval in 2016, and has been available in Europe since 2015. To date, it is employed for the treatment of calcified lesion in various vascular districts such as coronary, iliac, femoral, popliteal, infra-popliteal, and renal arteries [4, 5]. The novelty highlighted in our paper is about the use of the lithoplasty system to treat stent under-expansion due to calcified plaque.…”
Section: Discussionmentioning
confidence: 99%
“…The Lithoplasty system received FDA approval in 2016, and has been available in Europe since 2015. To date, it is employed for the treatment of calcified lesion in various vascular districts such as coronary, iliac, femoral, popliteal, infra-popliteal, and renal arteries [4, 5]. The novelty highlighted in our paper is about the use of the lithoplasty system to treat stent under-expansion due to calcified plaque.…”
Section: Discussionmentioning
confidence: 99%
“…The use of this technology for the treatment of peripheral arterial disease has recently been reported in the Disrupt BTK and Disrupt PADII studies. 8,9 In these studies, intravascular lithotripsy was demonstrated to be safe with minimal vessel injury and an average increase in vessel diameter of 3.0 mm. No perforation, distal embolization, or no-reflow phenomena were reported.…”
Section: Discussionmentioning
confidence: 99%
“…6 Intravascular lithotripsy, based on the principle of calcium disruption by sonic pressure waves first used in urology, has been introduced as a new method for calcified plaque modification in coronary and peripheral arteries. [7][8][9] In this case report, we report as the first the use of intravascular lithotripsy to enable transfemoral TEVAR in a patient with small caliber iliac arteries and circumferential calcified plaques.…”
Section: Introductionmentioning
confidence: 99%
“…The present analysis evaluates IPD from a pooled database of prospective studies of the Shockwave IVL device. The studies included in the present analysis are DISRUPT PAD I, II, III, BTK, and CFA . IPD for these studies were provided by the study sponsor (Shockwave Medical).…”
Section: Methodsmentioning
confidence: 99%
“…Representative case images before and after IVL therapy in a severely calcified right superficial femoral artery lesion are presented (Figure ). However, to date, this device has only been evaluated in small‐to‐intermediate sized nonrandomized studies . Therefore, we sought to perform an individual patient‐level data (IPD) pooled meta‐analysis of available IVL trials to assess the efficacy and safety of this technique in the treatment of moderately‐to‐severely calcified PAD lesions.…”
Section: Introductionmentioning
confidence: 99%